PEMBELAJARAN NUMBER HEAD TOGETHER DAN ING NGARSA SUNG TULADHA UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS - Eko Kristianto; Louise M Saija (LPPM Universitas Advent Indonesia, 2021)
Mathematical communication ability is important because it can train students thinking and reasoning, develop creative activities, develop problem solving skills and develop ability to convey information. But previous researchs shows that mathematical communication skill still not high, so it still needs to be improved. The purpose of this study is to know the Junior High School students' mathematical communication improvements, and whether there are different improvement between students who acquire Number Head Together cooperative learning model and Ing Ngarsa Sung Tuladha. This comparative designed study used 7 essay mathematical communication problems and response questionaire as the research instruments. The sample of this study were students in two grades VII of SMP Negeri 3 Parongpong, West Bandung. The result shows that the students’ mathematical communication improvement of those who acquire Number Head Together cooperative learning model and Ing Ngarsa Sung Tuladha are both in the moderate category, and they are not different statistically. Another result shows that students really like to learn using Number Head Together or Ing Ngarsa Sung Tuladha cooperative learning model.